2021
DOI: 10.1139/cjfr-2020-0447
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement learning in optimizing forest management

Abstract: We solve a stochastic high-dimensional optimal harvesting problem by reinforcement learning algorithms developed for agents who learn an optimal policy in a sequential decision process through repeated experience. This approach produces optimal solutions without discretization of state and control variables. Our stand-level model includes mixed species, tree size structure, optimal harvest timing, choice between rotation and continuous cover forestry, stochasticity in stand growth, and stochasticity in the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Stochastic phenomena with high relevance for timber production and carbon storage include fire hazard and pest damage, and as both of these are linked to the structure and quantity of living and dead trees in the stand, a model extension towards that direction would be interesting. These questions are recently studied in Malo et al (2021) but without carbon pricing. Also beyond the scope of this study are questions related to transaction costs e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic phenomena with high relevance for timber production and carbon storage include fire hazard and pest damage, and as both of these are linked to the structure and quantity of living and dead trees in the stand, a model extension towards that direction would be interesting. These questions are recently studied in Malo et al (2021) but without carbon pricing. Also beyond the scope of this study are questions related to transaction costs e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to asking how well the reduced model with a sparse state structure represents the original problem under study. Malo et al (2021) apply a size-structured matrix model with twelve pre-specified size classes, four tree species, and a continuous number of trees in each size class. Their matrix model is a direct simplification from a more detailed individualtree model obtained by a well-known transformation ( Getz and Haight, 1989 ).…”
Section: Related Literaturementioning
confidence: 99%
“…While the original PPO algorithm treats all actions as continuous, the algorithm can easily be modified to handle a mixture of discrete and continuous actions, where the continuous actions are viewed as parameters of the discrete actions ( Fan et al, 2019 ). Therefore, similar to Malo et al (2021) , we approach the problem of continuous action and state spaces using the notion of parameterized action spaces, where the choice between thinning, clear-cutting, and doing nothing is modeled as discrete actions and the actual harvesting quantities are modeled as their continuous parameters. Further details on the algorithm are discussed in Appendix D .…”
Section: We Writementioning
confidence: 99%
See 1 more Smart Citation
“…found reduced vulnerability of uneven-aged forests to natural disturbance. In a recent modelling study,Malo et al (2021) have demonstrated the economic advantage of a structurally diverse continuous cover forest to cope with natural disturbances in boreal spruce-pine forests Knoke et al (2021b). showed faster recovery of economic value of structurally heterogeneous forests, underlining their high resilience potential after high severity disturbance.…”
mentioning
confidence: 98%